2020
DOI: 10.3389/fpsyt.2020.00601
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Therapies in Functional Gastrointestinal Disorders: A Narrative Review and Clinical Implication

Abstract: The pathophysiology of functional gastrointestinal disorders (FGIDs) is still unclear and various complex mechanisms have been suggested to be involved. In many cases, improvement of symptoms and quality of life (QoL) in patients with FGIDs is difficult to achieve with the single-targeted treatments alone and clinical application of these treatments can be challenging owing to the side effects. Herbal preparations as complementary and alternative medicine can control multiple treatment targets of FGIDs simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 134 publications
0
27
0
Order By: Relevance
“…Moreover, enrichment of dietary linoleic acid (18:2), a precursor of bioactive conjugated linoleic acids [ 77 ], suggested that PA seeds might be a promising feed additive for ruminants. In addition, PA seeds have been widely used in Korean and Chinese traditional medicine for their roles in improving digestibility and intestinal motility (reviewed in [ 78 ]). Therefore, PA seeds could act as a source of fatty acids, probably replacing oil seeds that have been reported to decrease DM and neutral detergent fibre digestibility [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, enrichment of dietary linoleic acid (18:2), a precursor of bioactive conjugated linoleic acids [ 77 ], suggested that PA seeds might be a promising feed additive for ruminants. In addition, PA seeds have been widely used in Korean and Chinese traditional medicine for their roles in improving digestibility and intestinal motility (reviewed in [ 78 ]). Therefore, PA seeds could act as a source of fatty acids, probably replacing oil seeds that have been reported to decrease DM and neutral detergent fibre digestibility [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…• For those with postprandial distress syndrome, which is believed to be associated with problems in gastric emptying and accommodation, cyproheptadine is recommended as one of the first-line drugs 241,242 . The latest use of a peppermint oil-based preparation has also been shown to be beneficial [243][244][245] . The next step in treatment is the use of prokinetics, including 5-HT 4 agonists, and when those fail, 5-HT 1 receptor agonists such as buspirone, which relax the proximal stomach, are recommended 246 .…”
Section: Box 3 | Treatment Options For Functional Dyspepsiamentioning
confidence: 99%
“…Peppermint oil capsule is another herbal product that Alizia consumed daily to relieve bloating and flatulence. Peppermint oil is a safe and effective product for short-term treatment in functional GI disorders ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…The usage of integrative approaches in the alleviation of digestive symptoms is widely reported in the literature ( 8 12 , 14 , 15 ). The patient in this case report also experienced symptom control by following a modified dietary plan, consuming special diets and herbal products, and engaging in mind–body relaxation techniques.…”
Section: Lessons Learnedmentioning
confidence: 99%